Are declines in insects and insectivorous birds related?. Issue 1 (5th January 2021) - Tallamy, Douglas W; Shriver, W Gregory
Abstract: A flurry of recently published studies indicates that both insects and birds have experienced wide-scale population declines in the last several decades. Curiously, whether insect and bird declines are causally linked has received little empirical attention. Here, we hypothesize that insect declines are an important factor contributing to the decline of insectivorous birds. We further suggest that insect populations essential to insectivorous birds decline whenever non-native lumber, ornamental, or invasive plant species replace native plant communities. We support our hypothesis by reviewing studies that show (1) due to host plant specialization, insect herbivores typically do poorly on non-native plants; (2) birds are often food limited; (3) populations of insectivorous bird species fluctuate with the supply of essential insect prey; (4) not all arthropod prey support bird reproduction equally well; and (5) terrestrial birds for which insects are an essential source of food have declined by 2.9 billion individuals over the last 50 years, while terrestrial birds that do not depend on insects during their life history have gained by 26.2 million individuals, a 111-fold difference. Understanding the consequences of insect declines, particularly as they affect charismatic animals like birds, may motivate land managers, homeowners, and restoration ecologists to take actions that reverse these declines by favoring the native plant species that support insect herbivores most productively. Lay Summary: There may be a link between declining insect populations and bird population declines. Bird populations are often limited by the amount of insect food available to them. Most of the bird species that have declined in the last 50 years are those that depend on insects for food. One cause of insect declines is the widespread use of non-native plants in forestry and horticulture that do not support insects. The loss of insects, birds, and other forms of life is important because those are the species that run the ecosystems that support humans. One solution to this problem is to increase the populations of the insects that birds depend on by increasing our use of native plants in managed landscapes.